Decoding algorithmic literacy among journalists: Methodological tool design and validation for preliminary study in the Portuguese context - Foá, C.; Couraceiro, P.; Pinto-Martinho, A. (Observatorio (OBS*), 2024)
Recent developments in generative Artificial Intelligence (AI) have revitalized academic discourse on algorithmic systems, particularly on their potential, ethical considerations, risks, and regulatory challenges. Extensive research has examined how algorithms affect communication processes, focusing on their influence on news organizations, journalistic practices, public-media dynamics, media literacy, and combating disinformation and filter bubbles.An emergent strand of research defines and measures the multidimensional concept of algorithmic literacy. However limited research exists on the intersection of algorithmic literacy and journalism. This gap is particularly concerning given the pivotal roleof journalism in shaping public discourse, informing citizens, upholding democratic values and contrasting disinformation. Understanding how journalists perceive and engage with algorithms is essential, as these technologies significantly influence their professional tasks, including content production and distribution.In Portugal, where newcomer journalists work in precarious conditions and digital media transformation is rapidly evolving, understanding how journalists interact with and perceive algorithms is vital. Our study, through a multi-phased approach, aims to fill this gap questioning how can algorithmic literacy, encompassing cognitive, attitudinal and behavioural dimensions, be effectively assessed among professional journalists?The exploratory results present a validated methodological tool, instrument based on a multi-dimensional analytical framework and specifically designed to measure algorithmic literacy levels and to assess journalists’ experiences. Critical discussion addresses the methodological procedures and preliminary findings from the pre-test, offering insights into Portuguese journalists' understanding, perceptions, and competencies regarding algorithmic systems.By shedding light on the cognitive, affective, and behavioural aspects of journalists’ engagement with algorithms, this study contributes to a deeper understanding of the algorithmic literacy among journalists, which is essential to sustain the quality of their work and for an effective counteraction against disinformation. It also opens avenues for similar studies in other geographical or professional contexts.